Impact of N2O admixture on the characteristics of pulsed dielectric barrier discharges in N2 at atmospheric pressure. (22nd October 2019) - Höft, H; Kettlitz, M; Becker, M M; Brandenburg, R
Abstract: The impact of N2 O admixtures on the inception and development of pulsed dielectric barrier discharges (DBDs) in N2 at atmospheric pressure is studied using optical and electrical diagnostics supported by 0D modelling of the reaction kinetics. The N2 O concentration in the N2 –N2 O gas mixture was varied between virtually pure N2 and 10 vol% N2 O. A significant impact of N2 O on the discharge characteristics was found for concentrations above 1000 ppm. In particular, a decrease of the transferred charge, and discharge energy and an increase of breakdown voltage, maximal discharge current, discharge emission diameter and velocity of the cathode-directed ionisation front (positive streamer) were observed. Additionally, a strong increase of breakdown voltage and discharge inception jitter accompanied by a decrease of the emission duration was found for N2 O concentrations above 1 vol%. The modelling results indicate that for N2 O concentrations in this range a transition from an electropositive to an electronegative regime takes place.